Long noncoding RNA polymorphisms influence susceptibility to endemic pemphigus foliaceus3. (21st April 2019) - Lobo‐Alves, S.C.; Augusto, D.G.; Magalhães, W.C.S.; Tarazona‐Santos, E.; Lima‐Costa, M.F.; Barreto, M.L.; Horta, B.L.; de Almeida, R.C.; Petzl‐Erler, M.L.
Summary: Background: Pemphigus foliaceus (PF) is an epidermal autoimmune disease, characterized by the presence of autoantibodies against the desmosomal protein desmoglein 1. Genetic and environmental factors contribute to PF, a complex disease that is endemic in Brazil and Colombia and neighbouring countries, and in Tunisia. Long noncoding RNAs (lncRNAs) may participate in gene regulation by interacting with DNA, proteins and other RNAs. Dysregulation of lncRNAs has recently been recognized as an important coplayer in the onset or progression of complex diseases. In addition, single‐nucleotide polymorphisms (SNPs) located in lncRNA genes have been associated with differential risk to cancer, autoimmunity and infection. Objectives: Here, we aimed to investigate whether SNPs in lncRNA genes are associated with differential susceptibility to endemic PF. Materials and methods: We integrated data from the lncRNA SNP database with genome‐wide genotype data obtained for 229 patients and 6681 controls. We tested the association between endemic PF and 2080 SNPs located in lncRNAs applying logistic regression. Results: The most significantly associated SNP was rs7144332 (OR = 1·63, P = 2·8 × 10 –6 ), located in the lncRNA gene AL110292·1 . Results for five other SNPs were suggestive of association ( P < 0·001). In silico analysis indicated that five of the six SNPs impact transcription, three may influence lncRNA's secondary structure, and three may alter microRNA–lncRNA interactions. Conclusions: We showed, for the first time, that variation in lncRNA genes may influence pemphigus pathogenesis. Our findings highlight the importance of lncRNA variation in autoimmune and possibly other complex diseases and suggest polymorphisms for functional validation. Abstract : What's already known about this topic? The multifactorial autoimmune blistering skin disease pemphigus foliaceus (PF) presents a genetic susceptibility component that is not fully understood. Although PF is rare worldwide, it reaches a prevalence of 1·5–3% in some regions of Brazil, the highest ever reported for an autoimmune disease. Long noncoding RNA (lncRNA) polymorphisms have been associated with some complex diseases but have not yet been studied in any form of pemphigus. What does this study add? Genetic variation of lncRNA may influence susceptibility to PF via its effect on lncRNA structure, on transcription of nearby genes, and on microRNA–lncRNA interactions. We have shown, for the first time, that variation in lncRNA genes may influence PF pathogenesis. What is the translational message? Our findings show that lncRNA variation is part of the polygenic risk component in the pathogenesis of pemphigus and possibly other complex skin diseases, indicating that lncRNAs can be explored as potential new drug targets. Linked Comment:  Amber. Br J Dermatol 2019;181 :241–242 . Plain language summary available online Respond to this article